2017
DOI: 10.1007/s13205-017-0727-4
|View full text |Cite
|
Sign up to set email alerts
|

Production of biodiesel from microalgae through biological carbon capture: a review

Abstract: Gradual increase in concentration of carbon dioxide (CO 2 ) in the atmosphere due to the various anthropogenic interventions leading to significant alteration in the global carbon cycle has been a subject of worldwide attention and matter of potential research over the last few decades. In these alarming scenario microalgae seems to be an attractive medium for capturing the excess CO 2 present in the atmosphere generated from different sources such as power plants, automobiles, volcanic eruption, decomposition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
71
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(78 citation statements)
references
References 105 publications
0
71
0
7
Order By: Relevance
“…The complete utilization of algal biomass may comprise the association of different technologies (Behera et al, 2015). Algal lipids can be plucking out for production of biofuel and the residual solids, which are mostly proteins and carbohydrates are appropriate for larvae feeding (Mondal et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The complete utilization of algal biomass may comprise the association of different technologies (Behera et al, 2015). Algal lipids can be plucking out for production of biofuel and the residual solids, which are mostly proteins and carbohydrates are appropriate for larvae feeding (Mondal et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…It has also been reported that extracted microalgae such as Chlorococcum sp. improve the yield of yeast biomass by providing a sugar source for the yeast growth (Harun et al, 2010;Mondal et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Climate change and depletion of natural resources are two of the most threatening topics that concern the worldwide population nowadays; these were initially generated due to the rapidly increment in human population and the demanding lifestyle of the modern world. Dependence on the use of fossil fuels and their growing emissions requires the development of substitute energy sources; biodiesel production is considered the most prominent alternative to replace petroleum‐derived transport fuel . Biodiesel is a mixture of fatty acid alkyl esters obtained by transesterification of vegetable oils; the commonest are palm, soy, cotton, and sunflower, animal fats, and residues from food preparation have also been used.…”
Section: Introductionmentioning
confidence: 99%
“…It has been estimated that more than 50,000 species exist, but only around of 30,000 have been studied . Most of the microalgal species produce TAG along with other lipid types including phospholipids, glycolipids and sulfolipids; the main biological functions of these lipids are energy storage and cell signaling . The microalgal biodiversity is massive and each one has specific conditions for an optimum growth with respect to pH, nutrients requirement, temperature, oxygen, salinity, stirring speed, and time/light intensity.…”
Section: Introductionmentioning
confidence: 99%